The project of state transforma- tions by M.M. Speransky - M. A. Aleksenko; A. N. Popov; O. Yu. Malakhovа (Вестник Майкопского государственного технологического университета)
The relevance of the research lies in the analysis of the transformation project of one of the outstanding reformers of the days of Alexander I, whose ideas were not duly appreciated, but could prevent serious upheavals in Russia during subsequent reigns.   The problem is that changes proposed by Speransky’s would have laid the foundation for a deep reform of the country, however, not all projects were destined to be realized.   The purpose of the research is to consider the transformation projects of Speransky M.M. and to analyze the degree of their implementation.   The article used the retrospective and historical-genetic methods of historical research. The first allowed us to immerse ourselves in the events of the past, the second allowed us to analyze the degree of implementation of projects. The result of the research: many of Mikhail Mikhailovich’s proposals would subsequently be considered by the descendants of the winner of Napoleon Bonaparte, but then the Russian emperor considered the projects premature. Only the reform of religious educational institutions was one of the few that was implemented almost completely.   The conclusion: Speransky’s proposals in the field of religious education were implemented more than all others examined in the research; among state reforms, only the State Council arose; as for tax reforms, only certain partial proposals of the reformer were implemented.